Geopolitical teleconnections: Diplomacy, events, and foreign policy. (November 2019) - Clark, Julian; Jones, Alun
Abstract: We know little about how diplomacies narrate events to sustain state presence. This paper tackles this deficit, examining how foreign policy narratives try to tame the material-affective excess of events by asserting the fictive identity of states. To do so, we extend posthuman approaches to diplomacy by blending assemblage thinking with insights from topology on events to develop the concept of geopolitical teleconnections . We define this as diplomatic attempts to manipulate material-affective intensities between assemblages by tethering these intensities and the events they generate to state-sanctioned geohistories and policy narratives. Geopolitical teleconnections thus have potentially profound influence in mapping posthuman events onto the spatiotemporalities of states. We explore the utility of teleconnections as a conceptual scaffold through the empirical case of Iceland's turbulent geopolitics following the 2008 financial crisis. Our analysis shows how, despite intense diplomatic efforts, material-affective intensities actualised events that continually threatened to exceed Icelandic foreign policy narratives. In doing so it reveals the state as a congeries of assemblages and past-present-emergent events in teleconnected space-time, with diplomacy furnishing one means of giving a sense of permanency to something profoundly unstable. Moreover, geopolitical teleconnections expose foreign policy as a complex co-mingling of human and posthuman agencies, forceful in that they unsettle diplomatic bodies and destabilise diplomatic subjectivities by suddenly collapsing multiple times and spaces. In this way, the swarming multiplicities of events make myriad connections between diplomatic bodies and the body politic of the state.